Annotated record of the detailed examination of Mn deposits from R/V Robert Conrad Cruise 7 stations - Anderson, N D; Burckle, Lloyd H; Baker, R (Supplement to: Anderson, ND et al. (1963): R/V Robert Conrad Cruise 7 - Preliminary Megascopic Descriptions of Split Cores. Lamont Geological Observatory, Columbia University, New York, unpublished, 48 pp, 1963)
The cores and dredges described in this report were taken during the Robert Conrad Cruise 7 from July until October 1963 by the Lamont Geological Observatory, Columbia University from the R/V Robert Conrad . A total of 29 cores and dredges were recovered and are available at Lamont-Doherty Earth Observatory for sampling and study.